Winnipeg gathering of the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence series - Compton, Jim; Deerchild, Rosanna; Farmer, Gary; Kulchyski, Peter; Monkman, Lenard; Morrisseau, Miles; Ouellette, Robert-Falcon; Philips, Trevor; Spillet, Leslie; Wheeler, Kim; Buddle, Kathleen; Gagnon, John (2017)
A collection of documents, audio recordings, and programming resulting from the first gathering of the Future of First Nations, Inuit and Métis Broadcasting: Conversation & Convergence series held in Winnipeg, Manitoba on February 17th, 2017. Social Sciences and Humanities Research Council of Canada, Wawatay Communications Society, Community Media Advocacy Centre, CKWE 103.9FM, First Mile Connectivity Consortium, Forum for Research and Policy in Communications, Indigenous and Northern Affairs Canada - Strategic and Statistics Research Directorate, Media@McGill, University of Manitoba - Department of Anthropology, University of Ottawa - Department of Communication, University of Ottawa - Faculty of Arts, University of Ottawa, University of King's College, University of Alberta, CHUO, CKDU, UMFM, CFRT 107,3, l'Association des Francophones du Nunavut, and the World Association of Community Radio Broadcasters (AMARC)